Combios y continuidades en las relaciones internacionales = Changes and continuities in international relations. - RUSSELL, Roberto (1996)
Examines international relations from the perspective of three kinds of changes : the end of the cold war, the extension and deepening of globalization, and the Westphalian-type crisis. Concludes that in future world scenarios there will be continuities and changes and the opportunity to rescue the role of the State as the space from which it is possible to construct and legitimize spaces of international, regional, national and local governability.